Modeling Parkinson’s disease in midbrain-like organoids - Smits, Lisa M.; Reinhardt, Lydia; Reinhardt, Peter; Glatza, Michael; Monzel, Anna S.; Stanslowsky, Nancy; Rosato-Siri, Marcelo D.; Zanon, Alessandra; Antony, Paul M.; Bellmann, Jessica; Nicklas, Sarah M.; Hemmer, Kathrin; et al. (NPJ Parkinson's Disease, 2019)
Modeling Parkinson’s disease (PD) using advanced experimental in vitro models is a powerful tool to study disease mechanisms and to elucidate unexplored aspects of this neurodegenerative disorder. Here, we demonstrate that three-dimensional (3D) differentiation of expandable midbrain floor plate neural progenitor cells (mfNPCs) leads to organoids that resemble key features of the human midbrain. These organoids are composed of midbrain dopaminergic neurons (mDANs), which produce and secrete dopamine. Midbrain-specific organoids derived from PD patients carrying the LRRK2- G2019S mutation recapitulate disease-relevant phenotypes. Automated high-content image analysis shows a decrease in the number and complexity of mDANs in LRRK2- G2019S compared to control organoids. The floor plate marker FOXA2, required for mDAN generation, increases in PD patient-derived midbrain organoids, suggesting a neurodevelopmental defect in mDANs expressing LRRK2- G2019S. Thus, we provide a robust method to reproducibly generate 3D human midbrain organoids containing mDANs to investigate PD-relevant patho-mechanisms.